Response of Commercial Egg-Type Pullets to Diets Varying in Protein and Energy Content in Arid Hot Climate - Babiker, M.S.; Abbas, S.A. (International Journal of Poultry Science, 2009)
A 3 x 3 factorial arrangement was used in a completely randomized design to study three levels of protein and three levels of energy during several stages of pullet growing (starter, grower and developer) and their effect on growth and development. The experimental period was divided into four phases. Phase one (starter) from 0-6 wk, phase two (grower) from 7-12 wk, phase three (developer) from 13-18 wk and phase four (production). Data on phase four (production) are discussed elsewhere. In all phases of growth, control levels of protein and energy were set according to NRC (1994) and the other levels were higher and lower. A total of 9 treatments in all phases of growing were employed and each treatment was replicated three times with ten birds each. Lysine and methionine were added to the diets of all phases to meet levels recommended for birds in each growing phase (NRC, 1994). During the starter period three levels of protein (P1 = 16, P2 = 18 “control” and P3 = 20% CP) and Three levels of energy (E1 = 2650, E2 = 2850 “control” and E3 = 3050 kcal of ME/kg of diet) which equivalent (E1 = 11.1, E2 = 11.9 and 12.8 MJ/kg ME) were used. The same protocol in phase one was continued for the factorial arrangement for the grower period. The levels of energy were not change, but the levels of protein were changed (P1 = 14%, P2 = 16% “control” and P3 = 18%). For the developer period the same protocol in phase one and two was continued, but the levels of both protein and energy were changed (P1 = 13%, P2 = 15% “control” and P3 = 17%) and (E1 = 2700, E2 = 2900“control” and E3 = 3100 kcal of ME/kg of diet) which equivalent (E1 = 11.3, E2 = 12.1, and E3 = 13.0 MJ/kg ME). Body Weights (BW), Body Weight Gain (BWG) and Feed Consumption (FC) were measured and Feed Conversion (FCR) was calculated at the end of each growing phases. Higher protein levels consistently increased BWG of pullets during the starter (p<0.01) and grower periods (p<0.05). The body weights for pullets fed higher levels of protein (P2 and P3) were consistently higher than those fed lower protein level during all growing phases (p<0.01). High protein diets P2 and P3 during starter period resulted in improved FCR of birds compared to those pullets fed the low level of protein diet (p< 0.05). The best BWG and FCR during starter period were observed for birds fed P2E3 diet (p<0.01). BW, BWG and FCR were not influenced by dietary energy levels during all growing periods. The only exception for the BW and BWG during the starter period (p<0.05). FC was not affected by dietary protein and energy levels during the growing period. Oviduct development was affected by dietary protein and energy levels during the growing period (p<0.01). Ages at first egg and 50% production were advanced (p<0.05) due to the use of high protein diets. Thus, based on this study, birds fed high levels of protein diets (P2 and P3) during the early stages of growing period had the best BWG, BW and FCR and had well developed reproductive organs.